Hajj Fund Polemic (Between Subsidies and Istitha'ah) - Siti Ropiah (al-Afkar, Journal For Islamic Studies, 2024)
This research is aimed at demonstrating that an understanding of Istitha'ah in Islam is linked to subsidies carried out by the ministry of religious affairs (BPKH), in order that the performance of the hajj should be sharia. As a result of the increased "subsidy" carried out by the ministry of religions at the height of the subsidy burden, governments (the ministry of religions) should reexamine the "subsidy" policies. It is best that the ministry of religions no longer subsidize hajj candidates.  Not without cause or explanation. As the days of the future pilgrims became increasingly overcrowded. This suggests that the people of Indonesia have a wife in the practice of hajj. Other evidence is that many of the people voted for special hajj (plus) that would require far more than that of the regular hajj, which is a haji performed by the ministry of religions, to a few times more than that. Based on the above exposure, two formulas emerged:  (1) how to apply haji fund subsidies in Indonesia (2) how the status of stay 'ah is linked to haji fund subsidies. The study USES the type of normative legal research with a normative jurisdictional approach. Which involved a study of fatwa, books, and the opinions of the lawyers associated with the title. Research has shown that the application of subsidies to the hajj fund has not been consistent with the true requirement of the hajj requirement. If there is a subsidy, it is not such a subsidy as the ponzi system, which tends to include tyranny within it. It should be sourced by personal rather than collective, as has been the case, except for subsidies from apbn and were meant for the common good, such as haji officials.